Role of the tumour necrosis factor‐like weak inducer of apoptosis (TWEAK)/fibroblast growth factor‐inducible 14 (Fn14) axis in autoimmune thyroid disease. (28th July 2017) - Peng, Shiqiao; Yu, Xiaohui; Zhao, Xuemin; Wang, Xinyi; Sun, Xuren; Han, Cheng; Shan, Zhongyan; Li, Chenyan; Teng, Weiping
Summary: Background: TNF‐like weak inducer of apoptosis (TWEAK), its receptor fibroblast growth factor‐inducible 14 (Fn14) and its scavenger receptor CD163 (sCD163) have known associations with many autoimmune diseases. However, the role of the TWEAK axis in autoimmune thyroid disease (AITD) remains unclear. Therefore, the aim of this study was to investigate the role of the TWEAK‐Fn14 axis in the pathogenesis of AITD. Methods: Serum levels of soluble TWEAK (sTWEAK) and sCD163 were measured in 38 patients with Graves' disease (GD), 40 patients with Hashimoto's thyroiditis (HT) and 40 healthy controls (HCs). Additionally, the mRNA expression of TWEAK and Fn14 in peripheral blood mononuclear cells (PBMCs) was explored, and the protein expression of TWEAK and Fn14 in thyroid glands surgically removed from 10 patients with GD, 10 patients with HT and 10 HCs was studied by immunohistochemical staining. Results: The results showed that the serum levels of sTWEAK were significantly reduced in patients with HT and inversely correlated with antithyroid peroxidase antibody (TPOAb) levels. Additionally, high levels of sCD163 and a high sCD163/sTWEAK ratio were positively associated with the TPOAb levels in patients with HT and the thyrotropin receptor antibody (TRAb) levels in patients with GD. TWEAK mRNA expression and protein expression were upregulated in thyroid glands and PBMCs from patients with HT. Conclusion: Expression of the TWEAK‐Fn14 axis was upregulated in patients with AITD and might play a role in the pathogenesis of AITD.